Bank1 deficiency reshapes the gut microbiota of lupus mice towards an anti-inflammatory composition - Galicia, Georgina; Botía-Sánchez, María; Toro-Dominguez, Daniel; García, Ana López; Valera, Juan Rafael; Gómez Hernández, Gonzalo; Fernandez, Raquel Marcos; Carmona, Noelia; Luque, Gracia; Morell, María; Varela, Nieves; Pérez-Cozar, Francisco; et al. (Frontiers in Immunology, 2025)
The B-cell scaffold protein with ankyrin repeats (BANK1) regulates Toll-like receptor-7 (TLR7) signaling in B cells and its absence ameliorates lupus. Here, we investigated the involvement of Bank1 in the gut mucosal B cell response to commensals in a murine model of lupus. In health and disease, Bank1 deficiency resulted in changes in the intestinal IgA production levels that showed differential bacterial binding associated with a re-organization on the composition and structure of the gut microbiota. Furthermore, the amelioration of lupus gut pathology in mice lacking Bank1 was linked to the increase of Parabacteroides distasonis that when vertically transmitted or orally administered, as emerging probiotic, reduced disease severity and repaired signs of distorted intestinal permeability. The increase of P. distasonis directly correlated with anti-inflammatory processes. In vitro stimulation either with P. distasonis or via TLR9 allowed for the differentiation of IL-10 producing B cells which, in vivo, differentially accumulated in the Peyer´s patches of Bank1-deficient lupus mice. Finally, the blood microbiome of lupus patients was found to be devoid of P. distasonis, whereas healthy controls exhibited the bacterium, thereby supporting the protective role of P. distasonis in the disease.